Determinants of microenterprise performance among microcredit clients in urban areas of Malaysia - Mohamad Syahmi Mat Daud; Ku ‘Azam Tuan Lonik; Fazelina Sahul Hamid (Penerbit Universiti Kebangsaan Malaysia, 2023)
As one of the anti-poverty instruments, the potential of microenterprise in improving livelihoods through the promotion of self-employment activities and micro-entrepreneurship appears to have been increasing over time including in Malaysia. Therefore, this study aims to assess the determinants of microenterprise performance, with particular reference to microenterprise under the TEKUN Nasional microcredit scheme in urban areas of Malaysia. A conceptual framework is proposed considering a set of hypothesis, which were tested to a sample of 171 microcredit clients using random sampling method in Penang State, Malaysia. This study employed a descriptive analysis and multiple linear regression to analyze the primary data that was obtained through self-administered questionnaire. The results led to the conclusion that access to microcredit, previous experience, entrepreneurial values, and managerial competencies are predictors of microenterprise performance. The number of workers are also equally significant for the performance. The findings of this study suggests that finance per se is not sufficient in boosting the performance of microenterprise. The entrepreneurs and the enterprise attributes are equally important for microenterprise performance. Despite considerable attention on microcredit facilities, policy makers and practitioners in Malaysia should focus their energy to ensure their clients are highly competence in terms of entrepreneurial insights, managerial skills, basic experience and the stability of enterprises prior to venturing in microentrepreneurship activities particularly in urban areas.